2018
DOI: 10.4314/ahs.v18i3.20
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice towards cervical cancer among women in Finote Selam city administration, West Gojjam Zone, Amhara Region, North West Ethiopia, 2017

Abstract: Introduction: Cancer of the cervix is the leading cause of cancer-related death among women, especially in developing countries affecting women at a time of life when they are critical to social and economic stability. Method: The study was conducted at Finote Selam City Administration from February 01 to March 01, 2017 using a community-based cross-sectional study design. The representative sample size was selected using multistage sampling technique. The data were collected using an interviewer-administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 10 publications
2
21
1
Order By: Relevance
“…The analysis of the demographic data showed a higher percentage of females among the parents, reflecting the fact that mothers are usually the parent available to care for children even at adolescence. This study demonstrated that an average proportion of the parents were aware of cervical cancer, this can be compared to the findings of a study conducted in North West Ethiopia where 69.3% had heard about cervical cancer [ 20 ]. A study conducted among mothers in Somolu, an urban area in Lagos, found that 79.6% had heard about cervical cancer [ 21 ], however in another study in urban Lagos a lower proportion (37.2%) of respondents had heard about cervical cancer [ 22 ].…”
Section: Discussionmentioning
confidence: 57%
“…The analysis of the demographic data showed a higher percentage of females among the parents, reflecting the fact that mothers are usually the parent available to care for children even at adolescence. This study demonstrated that an average proportion of the parents were aware of cervical cancer, this can be compared to the findings of a study conducted in North West Ethiopia where 69.3% had heard about cervical cancer [ 20 ]. A study conducted among mothers in Somolu, an urban area in Lagos, found that 79.6% had heard about cervical cancer [ 21 ], however in another study in urban Lagos a lower proportion (37.2%) of respondents had heard about cervical cancer [ 22 ].…”
Section: Discussionmentioning
confidence: 57%
“…Screening and early treatment of cervical cancer if detected remains the most effective way to reduce the mortality associated with the disease. But different studies including in Ethiopia showed cervical cancer screening uptake is still low, ranged from 7.3 to 23.5% [ 9 – 14 , 35 – 37 ]. Concurrent to previous studies [ 12 , 20 , 35 – 38 ], our qualitative study revealed that lack of awareness or knowledge about cervical cancer and its causes, symptoms, fear of diagnosis and treatment among women decreased their participation rates in screening.…”
Section: Discussionmentioning
confidence: 99%
“…To achieved Ethiopia's 2020 ambitious goals, cervical cancer screening services are being provided free for all eligible women since 2016 [6]. Despite the availability of guideline for cervical cancer prevention and control; screening was not fully implemented in all health care centers [4] and its uptake among the community is still very low (7.3 to 23.5%) [9][10][11][12][13][14][15]. This could be attributed to lack of awareness about the importance and availability of cervical cancer screening services, perception about cancer, risk factors and prevention methods [12,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This finding correspond with finding from Continued another study done in Kinshasa. 27 This could be explained that women who reside in urban have more access to health information through media and ease access to health care as compared to those who are living in rural areas. Accordingly, this study having had a personal, familiar, or friendly history of cervical cancer were significant associated with an increased knowledge about cervical cancer, this is similar to findings from another study.…”
Section: Discussionmentioning
confidence: 99%